Remote laboratory: Application and usability - Schlichting, Luis C. M. (2017)
The practice and the hands-on are essential for technical and professionals skills, even in controlled situations. Due to that, the use of laboratories during the learning process is fundamental, although it has been more difficult to support such kind of infrastructure locally, which brings the challenge to find alternatives. On the other hand, the Brazilian law establishes that higher education institutions can offer a complete curricula or a part of the curricula by using E-learning, what builds a scenario to use remote laboratories. This work presents the alternatives for the use of remote laboratories, showing that this idea can be spread and applied in different technical areas allowing students and professors to accomplish experiments in a safe and flexible environment trough the internet in real remote laboratories. This work also shows preliminary discussions of a first experiment with technical high school students using remote laboratories.